PERAN PEKERJA SOSIAL DALAM PENGANGKATAN ANAK DI BALAI REHABILITASI SOSIAL ANAK YANG MEMERLUKAN PERLINDUNGAN KHUSUS “PARAMITA” MATARAM PROVINSI NUSA TENGGARA BARAT - Veggy Livian Agata; Meiti Subardhini; Ami Maryami (Politeknik Kesejahteraan Sosial Bandung, 2021)
The purpose of this research is to get an overview about how the role of social worker in the child adoption at the Social Rehabilitation Center of Child with Special Protection Need “Paramita” Mataram. To obtain an empirical description of the characteristics of informants, the role of social workers in adopting children as administrators, experts, enablers, brokers, advocates, and educators. The approach used in this study is a qualitative approach with a descriptive method. The techniques used are in-depth interviews, documentation studies and field observations. The informants determined by using purposive in total 2 (two) informants consisting of social workers who handle child adoption at BRSAMPK “Paramita” Mataram. The results of research on the role of social workers in adopting children at BRAMPK